Mixture of Five Fermented Herbs (Zhihuasi Tk) Alters the Intestinal Microbiota and Promotes the Growth Performance in Piglets - Li, Yong; Sun, Tiehu; Hong, Yuxuan; Qiao, Tong; Wang, Yongsheng; Li, Wei; Tang, Shi; Yang, Xin; Li, Jie; Li, Xiaowen; Zhou, Zutao; Xiao, Yuncai (Frontiers in Microbiology, 2021)
To explore the feasibility of using fermented Chinese herbal mixture Zhihuasi Tk (Z. Tk) supplementation to increase the swine production, we examined in vitro the protective effect of dietary supplementation with Z. Tk on the intestinal oxidative stress model and the regulation of both growth performance and intestinal microbiota of weaned piglets. Our results showed that the addition of Z. Tk increased the cell viability, prevented the decrease of glutathione peroxidase, and significantly increased the total antioxidant capacity and reduced the damage caused by H2O2 to the tight junction proteins of the porcine small intestinal epithelial cell line (IPEC-J2). Furthermore, weaned piglets supplemented with either 2 kg/ton zinc oxide (ZnO) or 4 kg/ton of Z. Tk in the diet increased body weight, average daily gain, and average daily feed intake, while the feed conversion rate and diarrhea rate decreased within 0-35 days. Results of the taxonomic structure of the intestinal microbiota showed that in 21 days after weaning, the Firmicutes/Bacteroidetes ratio in experimental group increased, while the Z. Tk increased the abundance of beneficial bacteria such as Lactobacillus and showed inhibitory effect on pathogenic bacteria such as members of Proteobacteria. In summary, dietary supplementation with Z. Tk maintained the intestinal microbiota in a favorable state for the host to effectively reduce the abnormal changes in the intestinal microbial structure and improved growth performance of weaned piglets. Therefore, Z. Tk may potentially function as a substitute for ZnO in feed additives for weaned piglets in modern husbandry.